STUDI LITERATUR PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KERJASAMA DALAM PERMAINAN HOKI - Muhamad Zainal Abidin, - (2021)
Tujuan penelitian literature review ini ingin mengetahui analisis penerapan model pembelajaran kooperatif untuk meningkatkan kerjasama dalam permainan hoki. Penelitian ini menggunakan desain literature review. Narrative literature review ini dipilih dalam desain penulisan artikel dengan Google Scholar, Science Direct, Tandfonline. Proses seleksi artikel menggunakan PRISMA flow chart dengan kriteria inklusi 1) Tahun publikasi 2011-2021; 2) Full access text ; 3) Terindex nasional atau internasional ; 4) Artikel ditulis dalam bahasa Inggris atau bahasa Indonesia. Hasil analisis 12 jurnal yang dikaji menunjukkan bahwa model pembelajaran kooperatif dapat meningkatkan kerjasama dalam permainan hoki. Kesimpulan penelitian yang dikaji dari 12 jurnal tersebut bahwa penerapan model pembelajaran kooperatif dapat meningkatkan kerjasama dalam permainan hoki. Kata Kunci : Pembelajaran Kooperatif, Kerjasama, Permainan hoki ABSTRACT Muhamad Zainal Abidin 1706171 LITERATURE STUDY OF THE APPLICATION OF COOPERATIVE LEARNING MODELS TO IMPROVE COOPERATION IN HOCKEY GAMES Supervisor Prof. Dr. Beltasar Tarigan, M.S. AIFO, H. Carsiwan, M.Pd. The purpose of this literature review research is to determine the analysis of the application of cooperative learning models to improve cooperation in hockey games. This study used a literature review design. This narrative literature review was selected in the design of writing articles with Google Scholar, Science Direct, Tandfonline. The article selection process uses the PRISMA flow chart with inclusion criteria 1) Publication year 2011-2021; 2) Full access text; 3) National or international indexed; 4) Articles written in English or Indonesian. The results of the analysis of the 12 journals studied show that the cooperative learning model can improve cooperation in the game of hockey. The conclusion of the research reviewed from the 12 journals is that the application of the cooperative learning model can increase cooperation in the game of hockey. Keywords: Cooperative Learning, Cooperation, Hockey Game